Postmodern geographies : the reassertion of speace in critical social theory - Soja, Edward W. (Verso, 1989)
Postmodern Geographies stands as the cardinal broadcast and defence of theory’s spatial turn. From the suppression of space in modern social science and the disciplinary aloofness of geography to the spatial returns of Foucault and Lefebvre and the construction of Marxist geographies alert to urbanization and global development, renowned geographer Edward W. Soja details the trajectory of this turn and lays out its key debates. An expanded critique of historicism and a refined grasp of materialist dialectics bolster Soja’s attempt to introduce geography to postmodernity, animating a series of engagements with Heidegger, Giddens, Castells, and others. Two exploratory essays on the postfordist landscapes of Los Angeles complete the book, offering a glimpse of Soja’s new geography carried into its highest register.